Značilnosti metode razlage na razredni stopnji osnovne šole - Sinkovič, Martina (Revija za elementarno izobraževanje, 2011)
Characteristics of the Method of Explanation at the Lower Level of Primary School. The article presents the method of explanation in primary school. The theoretical part introduces the concept of school, teaching as a communicative process and teaching methods in lessons. The method of explanation, its characteristics and types of explanations are presented in detail. The empirical work presents our survey which was carried out at the Jurij Dalmatin primary school in Krsko, where we observed the teaching of three different school subjects in the second grade for three weeks, and wrote down observations. We wanted to find out to which extent the method of explanation is represented at the lower primary level. We were also interested in analyzing a combination of different methods in the classroom, the success of this combination and the duration of the method of explanation in certain school lessons. School lessons were monitored by use of an observation sheet.